2015
DOI: 10.1186/s13000-015-0322-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: High doses of garlic extract significantly attenuated the ratio of serum LDL to HDL level in rat-fed with hypercholesterolemia diet

Abstract: BackgroundHypercholesterolemia is associated with an increased risk of heart disease. In this study, we investigated the antihyperlipidemic effects of garlic (Allium sativum L.) in rat models of hypercholesterolemic.MethodsWistar male rats were randomly divided into 4 diet groups with garlic supplementation. Male Wistar rats were fed by standard pellet diet (group I), standard diet supplemented with 4 % garlic (group II), lipogenic diet (containing sunflower oil, cholesterol and ethanol) equivalent to 200 mg r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The Editor-in-Chief and Publisher have retracted this article [1] because the scientific integrity of the content cannot be guaranteed. An investigation by the Publisher found it to be one of a group of articles we have identified as showing evidence suggestive of attempts to subvert the peer review and publication system to inappropriately obtain or allocate authorship.…”
Section: Retractionmentioning
confidence: 99%
“…The Editor-in-Chief and Publisher have retracted this article [1] because the scientific integrity of the content cannot be guaranteed. An investigation by the Publisher found it to be one of a group of articles we have identified as showing evidence suggestive of attempts to subvert the peer review and publication system to inappropriately obtain or allocate authorship.…”
Section: Retractionmentioning
confidence: 99%
“…[8,9] Efficacy of AS as antihyperlipidemic agent has been debated owing to diverging views of previous studies [10][11][12][13][14][15] in the CAD and PAD. However, recently published studies [10][11][12] have reported positive efficacy of AS against the CAD by cutting down the elevated blood cholesterol and lipids. Data from developing countries is lacking although AS is frequently used as food additive even in Pakistan.…”
Section: Allium Sativum (As)mentioning
confidence: 99%
“…Data from developing countries is lacking although AS is frequently used as food additive even in Pakistan. [11,13] Previous studies [13,14] had applauded its anti-hypertensive effects of ASE. A previous study [15] reported that the AS essential oil (ASEO) was effective in mobilizing the fat from fatty liver.…”
Section: Allium Sativum (As)mentioning
confidence: 99%
See 2 more Smart Citations